EFEKTIVITAS METODE COOPERATIVE LEARNING TIPE STAD DALAM MENINGKATKAN PEMAHAMAN BACAAN PADA MATA KULIAH DOKKAI 4 - Wardatun Hayati; Arza Aibonotika; Hana Nimashita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This study aims to determine reading comprehension in the Dokkai 4 courses after the application of the Cooperative Learning methods type Student Teams Achivement Divisions (STAD) with the learning design using JF Standard. This research used a weak experiment of one group pretest posttest design. Object of this research is Japanese languange education studensts at the University of Riau in 2016 class B consisted of 30 students. The sampling technique uses purposive sampling. The study applies two tests, pretest and posttest. Result of pretest and posttest were processed using test of Wilcoxon on The SPSS software. The pretest average score obtained by students was 39,5 and the posttest average increased to 78,3. Therefore there was a significant effect on reading comprehension in the subject after applying Cooperative Learning methods type Student Teams Achivement Divisions (STAD) in the 2016 Japanese languange education studensts class B at the University of Riau.Key Words: Dokkai, Cooperative Learning type STAD, JF Standar